Aesthetics and philosophy: The Power of Beauty in Christoph Menke’s Perspective - Galfione, María Verónica (Anales del Seminario de Historia de la Filosofía, 2021)
The present paper is aimed at rethinking the critical potentialities of the aesthetic experience. To this end, it reconstructs Christoph Menke’s aesthetic conception and determines how it articulates, on the one hand, a certain reconstruction of aesthetic modernity with a position on current art, and on the other, a radical defense of aesthetic negativity with the protection of social normative instances. In this sense, Menke’s approach involves both an intervention in the philosophical tradition and in the current debate, and can be understood, in turn, as an attempt at mediation between contemporary French philosophy and twentieth-century German thought. Nevertheless, in his positioning in the face of contemporary aesthetic debates, Menke seems to leave aside some of the main achievements of his reconstruction of aesthetic modernity, while in his attempt to articulate normativity and aesthetic negativity he finally turns artistic praxis itself into a model of successful social praxis. These problems are discussed towards the end of the article.
Keywords: Criticism; Aesthetics; Aesthetic modernity; Normativity